Reasons for seeking treatment for oral health problems in Medical Primary Care Clinics: a pilot mixed method study in Kuantan, Malaysia - Tin, Myo Han; Md Aris, Mohd Aznan; Sulong, Robiatu Adawiah (2014)
Limited oral health personnel who engage mostly in secondary care is one of the challenges for primary and emergency oral health care. There has been evidence of seeking treatment for oral health problems (OHPs) at medical primary care clinics (MPCCs) in the morbidity reports and oral health studies since the late 20th century. However, the reasons for seeking treatment at MPCCs are still unclear.